Mitigasi Risiko Self-Diagnose Melalui Media Sosial: Pengembangan Model Komunikasi Kesehatan Berbasis Digital - Vita Safira; Farida Nurul Rahmawati (PT. ALHAFI BERKAH INDONESIA, 2025)
Social media penetration reaching 60% of Indonesia’s population has transformed public health information-seeking patterns. The phenomenon of Self-Diagnose through social media, particularly among adolescents, poses significant health risks. This article employs a systematic literature review to analyze health communication strategies for mitigating Self-Diagnose risks. Results indicate that social media platform algorithms create echo chambers that promote normalization of health conditions and increase Self-Diagnose behaviors. Health misinformation spreads exponentially through viral sharing mechanisms. Effective communication strategies must integrate source credibility, accurate content quality, and optimal distribution mechanisms. The “Your Social Media is Not Your Doctor!” campaign is recommended to shift public paradigms. Comprehensive digital health communication policies through multisectoral collaboration are required.